The Meaning of Online Dating through Social Penetration Theory - Shepriyani Miftajanna; Irwansyah Irwansyah (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Online dating has changed the way people find dates from face-to-face to online meetings. Through internet media, the activity of exchanging personal information is a process of developing a relationship, before deciding to meet in person. One of the stages in the development of the relationship is self-disclosure (self-disclosure). Interpersonal relationships that continue to develop and build meaningful relationships can be done by studying the theory of social penetration. Altman and Taylor explain that social penetration is a pattern of developing a relationship. This study discusses the process of online dating users to build meaningful relationship patterns and develop into the self-disclosure side.